1997
DOI: 10.1161/01.atv.17.12.3489
|View full text |Cite
|
Sign up to set email alerts
|

Bcl I Polymorphism in the Fibrinogen β-Chain Gene Is Associated With the Risk of Familial Myocardial Infarction by Increasing Plasma Fibrinogen Levels

Abstract: The aim of this study was to investigate the association of the Bcl I beta-chain fibrinogen polymorphism with the risk of acute myocardial infarction (AMI) and its relationship with fibrinogen levels in the Italian population. We studied 102 AMI patients, selected within the framework of the GISSI-2 trial, who had a familial history of arterial thrombosis (at least one first-degree relative suffering from AMI or stroke before 65 years) and 173 control subjects (with neither AMI nor personal or familial history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 29 publications
2
39
2
3
Order By: Relevance
“…49 The BclI polymorphism has been shown to associate with increased fibrinogen levels and is more common in subjects with severe coronary artery disease. 50,51 The Ϫ455G/A substitution in the B␤ gene occurs in an IL-6 -responsive HNF1 element and has been associated with increased fibrinogen levels 52 in a manner that is environment-dependent. 53,54 In vitro studies of the B␤-455 A/G polymorphism have indicated that the substitution alters nuclear protein binding profiles, reporter luciferase gene expression, and that it may explain up to Ϸ11% of the variation in fibrinogen levels.…”
Section: Noncoding Polymorphisms Of Fibrinogen Genementioning
confidence: 99%
See 1 more Smart Citation
“…49 The BclI polymorphism has been shown to associate with increased fibrinogen levels and is more common in subjects with severe coronary artery disease. 50,51 The Ϫ455G/A substitution in the B␤ gene occurs in an IL-6 -responsive HNF1 element and has been associated with increased fibrinogen levels 52 in a manner that is environment-dependent. 53,54 In vitro studies of the B␤-455 A/G polymorphism have indicated that the substitution alters nuclear protein binding profiles, reporter luciferase gene expression, and that it may explain up to Ϸ11% of the variation in fibrinogen levels.…”
Section: Noncoding Polymorphisms Of Fibrinogen Genementioning
confidence: 99%
“…Increases fibrinogen level 50 More common in CAD [50][51] Fibrinogen B␤-148C/T --Fibrinogen B␤-448G/A Alters nuclear protein binding 55 More common in CAD [56][57][58] Coding polymorphisms…”
Section: Fibrinogen B␤ Bcl1mentioning
confidence: 99%
“…This might be explained by the reciprocal exchange that has taken place between the two populations ever since prehistoric times. For instance, during the late Neolithic period, north Sardinia saw the «Megalithic Circle» culture, that was in strong correspondence with the Haemostasis genes in Mediterranean populations 143 Zito et al, 1997;Dell'Acqua et.al., 1997;Iacoviello et al, 1998 North Italy 0.019 0.658 0.323 0.000 Girelli et al, 2000 Italy ( Peyruchaud et al, 1995;Ruan et al, 1993 England 0.730 0.850 0.810 0.883 0.046 0.672 0.282 0.000 Thomas et al, 1994;Humphries et al, 1996;de Knijff et al, 1994Netherland 0.710 0.830 0.861 de Maat et al, 1997de Knijff et al, 1994;Doggen et al, 2000 contemporaneous «Torreana» culture in Corsica. The contact between the two islands continued throughout both the Bronze and Iron Ages.…”
Section: Discussionmentioning
confidence: 96%
“…This allele variant has shown to be associated with an increased plasma fibrinogen level, which is an independent risk indicator for cardiovascular disease (de Maat et al, 1995;Iso et al, 1995;Zito et al, 1997;Donati et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation